TOMBSTONES WITH CHRONOGRAPHS FROM THE DAGESTAN VILLAGES OF SHINAZ AND GELHEN - Zakariaev, Zamir Sahbanovic (History, Archeology and Ethnography of the Caucasus, 2021)
The paper presents the results of the study of two Arabic language epigraphic monuments from the mountain villages of Shinaz and Gelhen. The unique nature of these well-studied tombstones lies in the fact that, apart from epitaphs, there are chronographs of historic events that took place in South Dagestan and neighbouring Shirvan in the 15th-early 18th centuries carved on them. We suggest a new reading of the Arabic texts on tombstones, as well as corrections in reading the historical chronographs. It has been revealed that the owner of the epitaph of the Shinaz stele of 1798–99 is a famous Dagestan researcher of the 18th century Isma‘il al-Shinazi. The previously unknown time of his life has also been reliably determined. An alternative dating of a similar stele from Gelhen, located on the grave of a representative of the hereditary spiritual elite of this village, ‘Abdurahman-effendi, son of malla Ibrahim, is proposed. The stele was made in 1848–49, exactly half a century after the Shinaz one. We came to conclusion that the source for the chronographs of both steles was not the chronograph created in 1710–12, as was previously believed. The direct source was the handwritten historical chronograph of Malij al-Rutuli from 1754–55. It is believed that the manuscript with the chronograph Malij al-Rutuli belonged to the scholar Sa‘id al-Shinazi, the son of Isma‘il al-Shinazi. It seems that Sa‘id al-Shinazi was the compiler of the entire text of the Shinaz stele on his father’s grave. It has been established that the texts of both steles contain excerpts from medieval Arabic poetry. The authors of these verses are the Caliph ‘Ali b. Abi Talib (d. 661) and the famous mystic of the ‘Abbasid era, Mansur al-Hallaj (d. 922). Al-Hallaj’s poems were first recorded in the epigraphy of Dagestan. The South Dagestan’s practice of including historical chronographs in the texts of tombstones, despite its rarity, undoubtedly testifies to the interest that representatives of the intellectual elite of Dagestan society showed to the study of history. The thesis of the close connection of epigraphic monuments of Dagestan with narrative texts has also been confirmed.